EMPLOYEE ENGAGEMENT PADA PT PJB - Fitriani, Arbania (Jurnal Psikologi : Media Ilmiah Psikologi, 2019)
This study aims to get an overview of Employee Engagement at PT PJB in Surabaya, East Java, Indonesia so that the information in this study can be used by the Directors and Management to develop a work culture that can encourage employee productivity. This research used non-experimental quantitative / EPF methods. The subjects of this study were employees of PT PJB who were permanent employees, not in work assignments, and had worked at PT PJB for at least 1 year. There are 10 Engagement indicators measured in the study , Cultural Reputation (RB), Career Management (MKa), Performance Management (Mki), Award Recognition (R), Work Environment (LK), Compensation Benefit (KB), Leadership (K), Team Cooperation (KT), Employee Development (PK), and Work Value (NK). The scale used is Likert scale using two scales, namely the Satisfaction Scale and the Urgency Scale where the sum of the distribution of satisfaction scales and urgencies will be defined as the engagement index. The results of frequency distribution showed satisfaction and Engagament presentation indices in PT PJB at 77.2% and 82.5%. This shows that employees at PT PJB already feel satisfied and interested in the organization where the factors that are considered to be the greatest percentage in encouraging satisfaction and engagement are factors of team collaboration. Based on multiple regression test, shows ttest > t table and p < 0,05 which means model and variables are valid. From the Regression model IKK = 74,690 + 0,011 RB + 0,060 MKa – 0,023 MKi + 0,013 RP + 0,001 LK - 0,013 KB + 0,0001 KP + 0,046 KT - 0,007 PK + 0,011 NK, can be concluded that every 1% increase in satisfaction on the Career Management indicator will increase engagement level by 0.06% and every 1% increase in satisfaction on the Team Cooperation indicator will increase the engagement rate by 0.046%.Keywords : Engagement, Employee Engagement